Structure–Activity Relationship of Propargylamine‐Based HDAC Inhibitors - Wünsch, Matthias; Senger, Johanna; Schultheisz, Philipp; Schwarzbich, Sabrina; Schmidtkunz, Karin; Michalek, Carmela; Klaß, Michaela; Goskowitz, Stefanie; Borchert, Philipp; Praetorius, Lucas; Sippl, Wolfgang; Jung, Manfred; et al. (ChemMedChem, 2017)
As histone deacetylases (HDACs) play an important role in the treatment of cancer, their selective inhibition has been the subject of various studies. These continuous investigations have given rise to a large collection of pan‐ and selective HDAC inhibitors, containing diverse US Food and Drug Administration (FDA)‐approved representatives. In previous studies, a class of alkyne‐based HDAC inhibitors was presented. We modified this scaffold in two previously neglected regions and compared their cytotoxicity and affinity toward HDAC1, HDAC6, and HDAC8. We were able to show that R‐configured propargylamines contribute to increased selectivity for HDAC6. Docking studies on available HDAC crystal structures were carried out to rationalize the observed selectivity of the compounds. Substitution of the aromatic portion by a thiophene derivative results in high affinity and low cytotoxicity, indicating an improved drug tolerance. Chirality and angle matter: Histone deacetylases (HDACs) play an important role in cancer, and their selective inhibition has been the subject of many studies aimed at finding new anticancer drugs. R‐configured propargyl amides and a thiophene linker inducing a slight kink in the linker moiety provide inhibitors of HDAC6 with significantly increased affinity, selectivity, and decreased cytotoxicity.